2021
DOI: 10.1021/acsami.1c02089
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Fabrication of Self-Healing and Injectable Carboxymethyl Chitosan Hydrogel Dressing for Wound Healing

Abstract: Herein, a new type of injectable carboxymethyl chitosan (CMCh) hydrogel wound dressing with self-healing properties is constructed. First, CMCh samples are homogeneously synthesized in alkali/urea aqueous solutions. Subsequently, trivalent metal ions of Fe3+ and Al3+ are introduced to form coordination bonds with CMCh, leading to an ultrafast gelation process. A series of hydrogels can be obtained by altering the concentration of CMCh and the relative content of metal ions. Owing to the dynamic and reversible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
92
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(105 citation statements)
references
References 55 publications
0
92
0
Order By: Relevance
“…Herein, we found that HaCaT cells were able to efficiently internalize PRP-Exos. It has been reported that a range of new types of hydrogels with specifically tailored biochemical functions can accelerate wound healing, thus exhibiting good prospects for therapeutic application [ 26 , 27 ]. However, such artificial hydrogels play a less direct role in normal physiological processes, and a combination of exosomes and hydrogels may thus offer greater advantages further expediting the wound healing process.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we found that HaCaT cells were able to efficiently internalize PRP-Exos. It has been reported that a range of new types of hydrogels with specifically tailored biochemical functions can accelerate wound healing, thus exhibiting good prospects for therapeutic application [ 26 , 27 ]. However, such artificial hydrogels play a less direct role in normal physiological processes, and a combination of exosomes and hydrogels may thus offer greater advantages further expediting the wound healing process.…”
Section: Discussionmentioning
confidence: 99%
“…Complete coordination and close contact between wound and dressings are expected to speed up hemostasis as well as improve regeneration efficiency. [ 37 ] Traditional hydrogel dressings are facile to form cracks under stress, which may affect integrity of the network structure, cause loss of function, and eventually be detached from the wound site prematurely. Furthermore, it was once demonstrated that hydrogels without compliance and self‐healing abilities could not manage the irregularly shaped injuries well, leading to a high probability of bacterial infection during wound treatment and delaying the rate of healing.…”
Section: Resultsmentioning
confidence: 99%
“…[ 38 ] In this context, hemostatic hydrogel dressings with excellent self‐healing behaviors can resist accidental tearing caused by wound activity or external forces, and therefore provide mechanical protection during the whole repair process. [ 37 ] Herein, our proposed hydrogels owned dynamic electrostatic interactions and reversible hydrogen bonds, which made them have a high potential of exhibiting an ideal self‐healing behavior ( Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Due to excellent biocompatibility and biodegradability, polysaccharides such as hyaluronic acid and chitosan are the most commonly used natural biopolymers in the wound dressing field ( Nosrati et al, 2021 ). For example, Cao et al (2021) prepared a novel carboxymethyl chitosan hydrogel used for wound healing, which exhibited thermoresponsive capacity to accelerate wound closure and surrounding tissues regeneration. Yang et al (2016) proposed a facile approach to produce a polyacrylamide–chitosan (PAM-CS) composite hydrogel with dramatically improved tensile strength and toughness, which can efficiently accelerate skin repair at different wound healing periods.…”
Section: Introductionmentioning
confidence: 99%